A Combined Behavioral Economics and Cognitive Behavioral Therapy Intervention to Reduce Alcohol Use and Intimate Partner Violence Among Couples in Bengaluru, India: Results of a Pilot Study. Issue 23 (December 2021) - Hartmann, Miriam; Datta, Saugato; Browne, Erica N.; Appiah, Prarthana; Banay, Rachel; Caetano, Vivien; Floreak, Rosii; Spring, Hannah; Sreevasthsa, Anurada; Thomas, Susan; Selvam, Sumithra; Srinivasan, Krishnamachari
Hazardous drinking is an important contributing factor to intimate partner violence (IPV) occurrence. However, only a limited number of community-based alcohol reduction interventions have been tested in low- and middle-income countries (LMICs) for their efficacy in reducing IPV. This pilot intervention study tested a 1-month combined behavioral economics and cognitive behavioral therapy intervention to reduce hazardous alcohol use and IPV in Bengaluru, India. Sixty couples were randomized to one of three study arms to test the effect of incentives-only and incentives plus counseling interventions compared with a control condition. Alcohol use among male participants was assessed using breathalyzer tests. Violence experienced by female participants was measured using the Indian Family Violence and Control Scale. Couples in the counseling arm participated in four weekly counseling sessions. Male participants in the incentive arms earned a reward for sobriety (breath alcohol concentration [BrAC] <0.01 g/dl). Results showed that while incentives reduced alcohol use, there was a greater proportion of negative BrAC samples among participants in the counseling arm compared with the control group (0.96 vs. 0.76, p = .03). Violence also decreased in both intervention arms. The estimated mean violence score for the counseling arm was 10.8 points lower than the control arm at 4-month follow-up visit ( p = .02). This study contributes important evidence to the field of alcohol reduction and IPV prevention approaches in LMIC settings and adds to the growing evidence that alcohol reduction is a modifiable means of addressing IPV.